1996
DOI: 10.1002/(sici)1096-9861(19960520)369:1<16::aid-cne2>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of nitric oxide synthase-containing ganglionic neuronal somata and postganglionic fibers in the rat kidney

Abstract: Nitric oxide synthase (NOS)-immunoreactive neurons were identified in the rat kidney by using an antibody against type Ia NOS and the avidin-biotin complex immunoperoxidase method in whole kidneys examined in 100 microns serial sections. The histochemical method for demonstration of the nicotinamide adenine dinucleotide phosphate diaphorase (NADPH-d) was also used to characterize NOS-containing neurons. All somata showing NOS immunoreactivity also displayed NADPH-d activity. The greatest number of neuronal som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Unidentified transmitters were suggested. Neuronal NOS-or NADPH diaphorase-positive nerves were detected in arcuate and interlobar arteries and preglomerular afferent arterioles in the rat and human kidney (Bachmann et al, 1995;Liu et al, 1996b) and dog and monkey kidney (Okamura et al, 1995d). In isolated perfused rabbit renal afferent arterioles contracted with norepinephrine, nicotine induced vasodilatation, and treatment with L-NA reversed the response to vasoconstriction (T. Tamaki, S. Kimura, and Y. Abe, unpublished observations), suggesting a release of NO from periarterial nerves.…”
Section: Renal Vasculaturementioning
confidence: 97%
“…Unidentified transmitters were suggested. Neuronal NOS-or NADPH diaphorase-positive nerves were detected in arcuate and interlobar arteries and preglomerular afferent arterioles in the rat and human kidney (Bachmann et al, 1995;Liu et al, 1996b) and dog and monkey kidney (Okamura et al, 1995d). In isolated perfused rabbit renal afferent arterioles contracted with norepinephrine, nicotine induced vasodilatation, and treatment with L-NA reversed the response to vasoconstriction (T. Tamaki, S. Kimura, and Y. Abe, unpublished observations), suggesting a release of NO from periarterial nerves.…”
Section: Renal Vasculaturementioning
confidence: 97%
“…Immunohistochemical studies have revealed staining for the superoxide dismutase (SOD), which is a scavenger for O 2 − , in neuronal nitric oxide synthase (nNOS)-containing nerves, and would have the potential of protecting NO from destruction by O 2 − (Liu et al 1997). The observation by Liu et al (1996), that there are nitrergic nerve fibres in the kidney which colocalize with sympathetic fibres, has been taken to suggest that a relationship exists between O 2 − and NO at the neuroeffector junction. The oxidative and antioxidant systems are normally in balance but under pathophysiological conditions, for example in hypertensive states, there are often altered levels of NO or O 2 − generation giving rise to accelerated NO removal and a blunting of its physiological role.…”
mentioning
confidence: 99%
“…However, the location of this nNOS was uncertain, although the nitrergic nerve fibers found in the kidney may be one of the important anatomical locations. 11 The aim of this study was to examine the potential influence of NO on the increased proximal tubular fluid reabsorption resulting from low level renal nerve stimulation and to elucidate which isoforms of NOS might be involved. This was performed by measuring the changes in proximal tubular fluid reabsorption in response to renal nerve stimulation following blockade of NOS using nonselective (L-NAME) and selective (7-NI and aminoguanidine) NOS inhibitors, as well as an NO donor (SNP) alone and together with L-NAME.…”
mentioning
confidence: 99%